An Empirical Evaluation of Data Integrity Algorithm Performance in Non-Relational Document Databases - Jamali, Mujeeb-ur-Rehman; Najma Imtiaz Ali; Imtiaz Ali Brohi; Muhammad Umar Murad; Yasir Nawaz; Uswa Urooj (VAWKUM transaction on computer sciences, 2023)
Non-relational document databases are a type of NoSQL databases, are gaining popularity owing to their flexibility, scalability, and performance. Document databases provide some distinct security issues. One of the most difficult security challenges is that they are frequently built to be extremely accessible. This can make them more vulnerable to assault if suitable security measures are not taken. Users of database can access data with weak authentication or authorization. Another issue is that they store data in a semi-structured or unstructured format. This makes it difficult to create and execute security safeguards. It may be difficult to detect and secure sensitive data that is kept. Document databases are certain data integrity problems. In this research work, we have developed Big Document DBCrypto’s architecture under which Middle ware provides users to use symmetric cryptography with any hashing algorithm or asymmetric cryptography with digital signatures to ensure data integrity.